Um quilombo no terreiro: território e identidade em Manzo Ngunzo Kaiango - Belo Horizonte/Minas Gerais - Ana Maria Martins Queiroz (2012)
The space-time experience of the subjects are different and are not determined exclusively by any dimension of reality, either, economic, social or cultural. In this sense, I understand that the processes of production of space are marked by different dynamics, which intertwine and define themselves, too, from the narratives and socio-spatial trajectories of different ethnic-racial groups. From this perspective, I point out that the city configures a plural space, in which territories are established, also plural. It is from this understanding that the present research framework, which aims to understand the process of constitution of territory quilombola Manzo Ngunzo Kaiango, located in the city of Belo Horizonte / MG, which is defined through the manifestation of the ethnic-religious candomble. The study seeks also to understand how relationships are established between the community and its surroundings, in order to identify how this group is perceived by the surrounding society. To development of this study used interviews, questionnaires and instruments of Participatory Rapid Diagnostic (PRD), which consists of a methodology to understand a given reality from the participation of the subjects involved in research, since they are those who build these diagrams and representations on the territory in which they live. The research consists, therefore, through the dynamic socio-spatial and identity of black people in the city, analyzing the peculiarities in the processes of formation of the territory of Manzo and the maintenance and reproduction of their cultural and religious, in order to discuss the issue of quilombos urban.